Implementasi Kecerdasan Emosional dalam Kepemimpinan Sekolah di SMK Muhammadiyah Suruh Kabupaten Semarang - Ida Zahara Adibah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2020)
This study intends to examine the implementation of emotional intelligence-based school leadership in SMK Muhammadiyah Suruh in Semarang Regency, where the researcher obtained the research indicators from the Fleishman’s dimension of leadership: initiating structure and consideration. From the initiative dimension are 1) leader’s ethos, 2) initiative intuition, and 3) allocation of responsibility, while from the dimension of leader’s consideration are 1) attention to works result and the process to gain it, as well as 2) attention to employee’s welfare. This qualitative research is employed with case study design and proceed with the data collection through interviews, participatory observation, and documentation studies. The results of this study are 1) the leader has implemented the leadership initiatives, proved by effective and efficient works by organizing rights and obligations of the school’s components, and 2) thanks to the excellent consideration, the leader could maintain a good condition of the school. The leader also continued to improve the employee’s welfare by increasing their income and successfully increase knowledge and skills both of the teacher and employee. Keywords: consideration, emotional intelligence, Fleishman, initiative, school leadership. Penelitian ini bertujuan untuk menguji implementasi kepemimpinan sekolah berbasis kecerdasan emosional di SMK Muhammadiyah Suruh Kabupaten Semarang, di mana peneliti menggunakan indikator penelitian dari dimensi kepemimpinan Fleishman: inisiatif dan perhatian. Dari dimensi inisiatif terdapat 1) etos pemimpin, 2) intuisi inisiatif, dan 3) alokasi tanggung jawab, sedangkan dari dimensi perhatian pemimpin adalah 1) perhatian pada hasil karya dan proses untuk mendapatkannya, serta 2) perhatian pada kesejahteraan karyawan. Penelitian kualitatif ini menggunakan desain studi kasus dan dilanjutkan dengan pengumpulan data melalui wawancara, observasi partisipatif, dan studi dokumentasi. Hasil penelitian ini adalah 1) pimpinan sekolah telah melaksanakan inisiatif kepemimpinan, dibuktikan dengan kerja efektif dan efisien dalam mengatur hak dan kewajiban warga sekolah, dan 2) berkat perhatian yang sangat baik, pimpinan dapat memelihara kondisi sekolah dengan baik. Pimpinan juga terus meningkatkan kesejahteraan karyawan dengan meningkatkan penghasilannya dan berhasil pula meningkatkan pengetahuan dan keterampilan baik bagi guru maupun karyawan. Kata kunci: Fleishman, inisiatif, kecerdasan emosional, kepemimpinan sekolah, perhatian